Korelasi Antara Indeks Pembangunan Manusia (IPM) dan Pertumbuhan Ekonomi Regional di Kabupaten Probolinggo Tahun 2020–2024 - Afton Ilman Huda; Muhammad Jaiz; Ridwanul Hayat; Miftahul Ulum; Fhatoni; Ahmad Syahrul Khoir Maulana; Wahyu Ilahi; Muhammad Pradipta Baskara; Mohammad Khomisun; Much Fakhri; Moh Fikri Rizal (CV. ITTC INDONESIA, 2025)
This research explores the relationship between the Human Development Index (HDI) and regional economic growth in Probolinggo Regency during 2020–2024. HDI represents not only education and health, but also the overall quality of life of the population. On the other hand, economic growth is measured using the Gross Regional Domestic Product (GRDP) at constant prices. This study applies a quantitative approach using secondary data from the Central Bureau of Statistics (BPS), with Pearson correlation analysis to examine the link between the two variables. The results show a positive and meaningful correlation, suggesting that improvements in human development tend to go hand in hand with better economic performance. These findings emphasize that developing human capital is not just a social priority, but a strategic move to build sustainable regional growth.